2010
DOI: 10.1021/jp1035426
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Adsorption Effects on Metal Phthalocyanines

Abstract: The adsorption of nitric oxide (NO) on various metal phthalocyanines (MPc, M = Mn, Fe, Co) has been studied using first-principles calculations based on density functional theory (DFT). In this study, we investigated the fully optimized geometries and electronic structure of MPc. We found that the electronic structures of metal atoms are essential in shaping the ground-state electronic structure near the Fermi level. These states are defined mostly by the d orbitals of the transition-metal atoms and, to some d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…This was checked by calculating the adsorption energy of NO on a more reactive MPc. For NO/CoPc, the DFT VASP plane wave calculation gives a binding energy of 1.57 eV, which agrees well with the binding energy of 1.55 eV calculated by Nguyen et al 47 for the same system, which also used the VASP plane wave code. It is noted that other computational methods give slightly higher binding energies; atomic-orbital DMol simulations of Lozzi et al showed a binding energy of 0.40 eV for NO 2 / CuPc.…”
Section: Resultssupporting
confidence: 86%
“…This was checked by calculating the adsorption energy of NO on a more reactive MPc. For NO/CoPc, the DFT VASP plane wave calculation gives a binding energy of 1.57 eV, which agrees well with the binding energy of 1.55 eV calculated by Nguyen et al 47 for the same system, which also used the VASP plane wave code. It is noted that other computational methods give slightly higher binding energies; atomic-orbital DMol simulations of Lozzi et al showed a binding energy of 0.40 eV for NO 2 / CuPc.…”
Section: Resultssupporting
confidence: 86%
“…The coordination of CO and NO to metal ion of metal phthalocyanine, metal porphyrine, and their derivatives has been widely investigated from the viewpoints of coordination chemistry and biological chemistry. [28][29][30] A universal trend on the coordination geometry has been found that the CO molecule takes an upright configuration while the NO molecule favors the tilting configuration. This universal trend is true for the FePc adsorbed on Au(111).…”
Section: A Geometric Structure Of Coordinated Fepc Complexesmentioning
confidence: 98%
“…The structures of MPc and NO-adsorbed MPc (MPc-NO) were fully optimized until the Hellmann-Feynman force exerted on an atom was less than 0.05eV/Å. The most stable structure of NO on MPc was found by optimizing several initial adsorption sites of NO related to MPc surface as discussed elsewhere [27], where NO molecule is placed on top of the metal atom of MPcs. The binding energy of NO with MPc is calculated from following expression: ∆E = EMPc+NO -(EMPc -ENO).…”
Section: Methodsmentioning
confidence: 99%